Signaling pathways implicated in enhanced stem/progenitor cell differentiation on electroactive scaffolds - Heng, Boon Chin *; Bai, Yunyang; Li, Xiaochan; Meng, Yanze; Zhang, Xuehui; Deng, Xuliang (Elsevier, 2022)
Cells are naturally surrounded by an electroactive extracellular matrix in vivo, which is composed of a diverse array of charged molecules such as glycosaminoglycans and proteoglycans, together with piezoelectric collagen fibers capable of generating electrical signals in response to mechanical stimuli. In recent years, electroactive scaffold materials have attracted much attention in tissue engineering and regenerative medicine applications, as a biomimetic strategy to recapitulate the natural physiological electrical microenvironment in vivo, which could enhance the differentiation of stem/progenitor cells into specific lineages, thus facilitating tissue repair and regeneration. The key to improving the functional design of electroactive scaffold biomaterials would be to understand the various intracellular signaling pathways that are activated by electrical stimuli. Therefore, this review critically examines the effects of electrical stimuli and/or scaffolds with electroactive properties on directing stem/progenitor cells towards the osteogenic, neurogenic and other lineages, with particular focus on the molecular signaling pathways involved.